The machine question critical perspectives on AI, robots, and ethics - Gunkel, David J. (MIT Press, 2012)
An investigation into the assignment of moral responsibilities and rights to intelligent and autonomous machines of our own making.
Keywords: Robotics -- Human factors.; Robotics -- Moral and ethical aspects.; Robotics -- Philosophy.; Artificial intelligence.; elektronické knihy; electronic books